The impact on the current developments of the Central Bank of Iraq on activating bank credit for the private commercial banking sector (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Central banks want adequate control and supervision of credit because of the substantial credit risks they face, which may even affect the reputation and faith of the banking system as a whole. Central banks ' supervisory monitoring of banks has various advantages, including ensuring the financial stability of banks as a whole, stabilizing the overall level of prices, as well as safeguarding the rights and finances of depositors, shareholders and investors.The main role of supervisory oversight is to control credit by controlling it from excessive expansion in periods of economic inflation or its activation, and to improve and expand credit currencies in situations of economic recession, or when central banks wish to support the national economy or a sector of various economic sectors. Financial indicators provided by the Central Bank have been used to control government and commercial institutions operating under its supervision. These indicators have been used to a number of private banks, including Egypt, Baghdad and Babylon.The research has reached several important conclusions, including that the supervisory oversight of central banks has an important role to play in protecting the banking system as a whole and maintaining public and private funds at the same time in accordance with their laws, instructions and practices. Central banks have their own methods by which they can manage and control the level of bank credit. At the same time, central banks can identify other solutions that can increase credit activity by changing techniques of surveillance and the use of advanced electronic tools.As a result of the application of these indicators, there is a weak correlation between the supervisory oversight of the Central Bank in stimulating the credit policies of the private commercial banking sector and the fact that banks do not have in-depth plans to stimulate bank credit at the same level as they do in maximizing profits by relying on another source of profit, namely, the foreign exchange window and foreign transfers.